Bagaimana Alokasi Anggaran Berhubungan dengan Kualitas Infrastruktur Jalan di Indonesia? - Damayanti, Made Tara; Abbas, Yulianti (EQUITY, 2025)
Financial reports in the context of government are a means of accountability for regional financial management during a certain period. This study aimed to examine whether components of local government financial statements can be effectively used to evaluate performance in managing spending and revenue collection. To achieve the aim, the association of road quality with infrastructure spending and motor vehicle tax revenue was investigated, using fiscal independence as a moderating factor. The investigation was conducted using data from 341 regencies across Indonesia from 2017 to 2022. The result showed that infrastructure spending was negatively associated with improvements in road quality. Meanwhile, motor vehicle tax revenue was not associated with the improvements in road quality. The relationship between spending and road quality was particularly pronounced in Eastern Indonesia compared to Western regions, and regions with lower fiscal independence. Keywords: Decentralization; Infrastructure Spending; Motor Vehicle Tax; Road Quality; Indonesia.